2023
DOI: 10.1007/s10453-023-09780-z
|View full text |Cite
|
Sign up to set email alerts
|

Automatic real-time monitoring of fungal spores: the case of Alternaria spp.

Abstract: We present the first implementation of the monitoring of airborne fungal spores in real-time using digital holography. To obtain observations of Alternaria spp. spores representative of their airborne stage, we collected events measured in the air during crop harvesting in a contaminated potato field, using a Swisens Poleno device. The classification algorithm used by MeteoSwiss for operational pollen monitoring was extended by training the system using this additional dataset. The quality of the retrieved con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The first model investigated uses a convolutional neural network (CNN) that employs only the two holographic images as input ("Holo.-Only"). This model differs from models used in previous studies of bioaerosol identification (Sauvageat et al, 2020;Erb et al, 2023a) The model training resulted in an overall accuracy of 90% on the test dataset. Particle types that share size and shape characteristics perform worse than those with defining features, such as pollen.…”
Section: Particle Classification Using Machine Learningmentioning
confidence: 74%
See 3 more Smart Citations
“…The first model investigated uses a convolutional neural network (CNN) that employs only the two holographic images as input ("Holo.-Only"). This model differs from models used in previous studies of bioaerosol identification (Sauvageat et al, 2020;Erb et al, 2023a) The model training resulted in an overall accuracy of 90% on the test dataset. Particle types that share size and shape characteristics perform worse than those with defining features, such as pollen.…”
Section: Particle Classification Using Machine Learningmentioning
confidence: 74%
“…Digital holography can provide improved information about aerosol particle size and shape beyond other light scattering methods (Berg et al, 2017) and has been demonstrated for various coarse-mode particles, including bioaerosol (Sauvageat et al, 2020;Erb et al, 2023a), ice crystals (Touloupas et al, 2020), and more (Berg et al, 2017). The SwisensPoleno is a powerful instrument to capture a diverse range of single-particle morphology in near real-time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 51 , 52 Most systems have, to date, focused on the main pollen types present in Central Europe. However, many research groups are actively working to extend the current capabilities to fungal pathogens 53 , 54 and other types of particles (e.g., Šikoparija et al. 55 ), in convergence with aerosol and air quality observations.…”
Section: Automated Monitoringmentioning
confidence: 99%